Factors Affecting Post-Operative Mortality Rate after Major Lower Extremity Amputations in a Tertiary Institution in Singapore - Ong Ee Teng; Ng Shin Yi; Yang Yong; Thong Sze Ying (Research and Practice in Anesthesiology, 2017)
Background: Non-traumatic Major Lower Extremity Amputation (MLEA) surgeries are associated with high post-operative morbidity and mortality rates. There are few studies evaluating factors associated with post-operative mortality rates for MLEA among Asian patients. Objective: To identify factors that affect post-operative mortality rate and ICU admission rates in patients undergoing non-traumatic MLEA surgeries in a tertiary institution in Singapore. Method: A retrospective study was performed by using the operating theatre electronic database to identify patients who underwent non-traumatic MLEA surgeries in Singapore General Hospital during the period of January 1, 2010 to December 31, 2011. Results: Data was collected from 186 non-traumatic MLEA surgeries performed during the study period. Overall post-operative in hospital mortality rate was 8.6%, higher for above knee amputation (AKA), than Through Knee Amputation (TKA) than Below Knee Amputation (BKA) (18.4% vs. 8% vs. 4.5%, p=0.015). In multivariate logistic regression analysis, site of amputation of AKA compared to BKA (odds ratio 3.9, 95% confidence interval 1.1-14.5, p=0.04), ASA 4 status (odds ratio 4.3, 95% confidence interval 1.2-14.6, p=0.02) and presence of septic shock (odds ratio 4.9, 95% confidence interval 1.4-17.3, p=0.01) were significant predictors of post-operative in hospital mortality rate. The same 3 factors were significant predictors of post-operative ICU admission rate. Use of peripheral nerve block as the sole anaesthetic technique did not affect in-hospital mortality rate (adjusted odds ratio 1.3, 95% confidence interval 0.3-5.6). Conclusion: Patients with ASA 4 status and pre-operative septic shock, especially those under going AKA, should be considered as high risk group and therefore managed appropriately. The higher incidence of post-operative ICU admission rate in this group of patients also necessitates pre-operative organization of bed availability. Using peripheral nerve block as the sole anaesthetic technique did not significantly affect outcomes measured.